IMPLEMENTASI PROGRAM MORNING SPIRITUAL GATHERING SEBAGAI UPAYA PEMBENTUKAN KARAKTER RELIGIUS (Studi Kasus Pada Guru-Guru SMK Muhammadiyah 1 Sukoharjo) - Sahana, Bambang; Sumarno, S.; Suharjo, Sri (Sebelas Maret University (UNS), 2017)
This study aims to describe the implementation of the program Morning Spiritual Gathering (MSG) in an attempt to form a religious character in teachers at Vocational secondary school Muhammadiyah 1 Sukoharjo. This type of research is a qualitative single case study with strategy. Data source this study informants, places and events, as well as documents. Using data collection techniques interviews, observation, documentation, and FGD. Test the validity of the data in this study using triangulation techniques, sources, and researchers. The data obtained were analyzed using analysis of interactive models, Miles and Huberman.The results showed that the Program Morning Spiritual Gathering (MSG) conducted on teachers in Secondary Vocational School Muhammadiyah I Sukoharjo really aiming to form a religious character. MSG makes the existence of a growing activity and increased faith in teachers. Implementation of MSG every morning, at 7 am EST, at 06-done on the school, location, circumstantial. The process of internalization of the values it embodied with refraction conducted by school through MSG. Various obstacles faced in the activities of MSG in Secondary Vocational School Muhammadiyah I Sukoharjo in shaping religious character is resolved by collaboration between teachers.